2014
DOI: 10.4103/2008-322x.150827
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness and amblyopia

Abstract: Purpose:To compare macular thickness in children with functional amblyopia and those without amblyopia using optical coherence tomography (OCT).Methods:This case-control study was conducted on 93 children aged 3–10 years including 44 cases with unilateral amblyopia and 49 subjects without amblyopia. Amblyopic eyes were considered as the case group and their fellow eyes as internal controls; eyes of non-amblyopic children served as the external control. Macular thickness of all eyes were measured by optical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
3
18
2
Order By: Relevance
“…The mean BCVA of the amblyopic eyes was less than that of both internal and external controls, and the BCVA of the internal controls was also less than that of the external control group ( p < 0.001), as seen in our previous study [ 14 ]. This may be due to the existence of subtle variability in visual function in the healthy eye of unilateral amblyopic children.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The mean BCVA of the amblyopic eyes was less than that of both internal and external controls, and the BCVA of the internal controls was also less than that of the external control group ( p < 0.001), as seen in our previous study [ 14 ]. This may be due to the existence of subtle variability in visual function in the healthy eye of unilateral amblyopic children.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, there was a significant difference in macular retinal thickness at the center and 1-mm ring area in the moderately to severely amblyopic eyes compared to the non-amblyopic controls ( Table 4 ), although this difference was not found in the previous study conducted by the same author on mildly amblyopic children [ 14 ].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This might be due to the exclusion of extreme errors or severe amblyopia from the study. This was in agreement with the conclusions of Rajavi et al 54 However, to substantiate these results, a survey with a large sample size will be required including severe amblyopia.…”
Section: Discussionsupporting
confidence: 91%
“…- Rajavi (2014) showed that the average foveal thickness of children with moderate and severe amblyopia was 10 microns thicker compared with the congener eye or the control group. Also, male patients had a mean macular thickness thicker than female patients and there was no correlation between the types of amblyopia and macular morphology changes [ 12 ];…”
Section: Resultsmentioning
confidence: 99%